Interview of Nathaniel C. Gerson by Brian Shoemaker - Gerson, Nathaniel C. (Byrd Polar Research Center Archival Program, 2006)
Key Individuals Mentioned Dr. Sarle, pp. 11 Gordon Dunn, pp. 13 David Fuchs, pp. 13 Facando Bueso, pp. 14-15 Dr. George W. Kendrick, pp. 15-17, 22-24, 33 Louis P. Harrison, pp. 18-20 _____ Wexler, pp. 20, 22 F.W. Weikeldurer, pp. 23 Captain Albert C. Trakowski, pp. 31, 65-66 Colonel Higgenson, pp. 33, 58 General Kohl, pp. 63 Dr. Newman, pp. 67-68 Dr. Korff, pp. 67 Dr. Haurowitz, pp. 67 General Rives, pp. 70 Colonel Westburn, pp. 72 ______Kruschev, pp. 72 General Bernard Shrever, pp. 72 Colonel Joe Fletcher, pp. 76, 78 Henry Booker, pp. 78-79 Dr. Demigar, pp. 79-80 ______ Greenberg, pp. 85 Joseph Kaplan, pp. 94-95, 97 ______ Berkener, pp. 97, 100-101 Marcel Nicolet, pp. 98 Sidney Chapman, pp. 98 ______ Audeshaw, pp. 100 ______ Shapley, pp. 100 ______ Stillhouse, pp. 100 ______ Bulkeley, pp. 101-102 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Nathaniel_Gerson_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Nathaniel_Gerson_2.mp3 Gerson, a participant in the IGY (International Geophysical Year) begins his interview with the discussion of his time in Civil Service with the Railway Mail System between Washington, D.C. and Boston in the 1930s. During his time with the Mail System he continued to take various Civil Service exams and eventually, in August of 1938(39) he was given an appointment at the US Weather Bureau. This was his introduction to science and meteorology. Gerson worked as a meteorological observer in the Boston office, casting maps of current weather conditions to be printed for distribution. The Bureau eventually assigned Gerson to San Juan, Puerto Rico so that he could go to the University of Puerto Rico at night to earn his degree in Physics. While in San Juan, Gerson worked at the Hurricane Center, releasing radiosohn balloons all night and sending the data gathered to Washington, D.C. When his degree was complete, Gerson moved to a Weather Bureau job in Washington, D.C, where he developed ...